2021
DOI: 10.1038/s41467-021-24769-3
|View full text |Cite
|
Sign up to set email alerts
|

NEK2 inhibition triggers anti-pancreatic cancer immunity by targeting PD-L1

Abstract: Despite the substantial impact of post-translational modifications on programmed cell death 1 ligand 1 (PD-L1), its importance in therapeutic resistance in pancreatic cancer remains poorly defined. Here, we demonstrate that never in mitosis gene A-related kinase 2 (NEK2) phosphorylates PD-L1 to maintain its stability, causing PD-L1-targeted pancreatic cancer immunotherapy to have poor efficacy. We identify NEK2 as a prognostic factor in immunologically “hot” pancreatic cancer, involved in the onset and develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 77 publications
(60 citation statements)
references
References 54 publications
1
59
0
Order By: Relevance
“…8 24 To address some of these obstacles, recent studies, including our previous published work, have suggested therapy comprizing combinations of immune costimulation-based strategies that could markedly augment the immune treatment effect against PDAC. [25][26][27] In theory, targeting TNFR2 might modulate immunological features and remove the immunosuppressive PDAC TME, thus increasing anti-PD-L1 therapy's antitumor activity. The present study aimed to assess the function and mechanism of TNFR2 in PDAC and the potential of a combination of TNFR2 blockade and PD-L1 blockage to treat pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…8 24 To address some of these obstacles, recent studies, including our previous published work, have suggested therapy comprizing combinations of immune costimulation-based strategies that could markedly augment the immune treatment effect against PDAC. [25][26][27] In theory, targeting TNFR2 might modulate immunological features and remove the immunosuppressive PDAC TME, thus increasing anti-PD-L1 therapy's antitumor activity. The present study aimed to assess the function and mechanism of TNFR2 in PDAC and the potential of a combination of TNFR2 blockade and PD-L1 blockage to treat pancreatic cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Inhibition of NEK2 thereby sensitizes PD-L1 blockade and synergistically enhances the immune response against pancreatic cancer. Combinatorial inhibition of NEK2 and PD-L1 significantly improves therapeutic efficacy in pancreatic cancer in preclinical models [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…T cells can gain the ability to eliminate tumor cells by expressing PD-1 ( 41 ). However, tumor cells and APCs can express PD-L1, the ligand of PD-1 ( 42 , 43 ) ( Figure 1 ). By binding to PD-1, TIL apoptosis is induced on the one hand and CD4+ differentiation into regulatory cells (Treg) is stimulated on the other hand ( 44 , 45 ).…”
Section: Dna Damage Repair Is Related To Innate Immunity and Tumor Immune Escapementioning
confidence: 99%